Familial Hashimoto's thyroiditis with kidney impairment. Issue 8 (August 1987) - Shuper, A; Leathem, T; Pertzelan, A; Eisenstein, B; Mimouni, M
Abstract : A 12 year old boy and his two sisters with Hashimoto's thyroiditis and renal impairment were studied. Three generations of this family had autoimmune thyroid disease: Graves' disease was diagnosed in the first generation, and the second and third generations had thyroid enlargement with abnormal thyroid function and immunological abnormalities. The disease in this family could not be explained simply by the types of human leucocyte antigens found. Renal disease in autoimmune thyroid disease is uncommon, treatment difficult, and the prognosis unknown. The proteinuria disappeared in all three children during the three and a half years of follow up, which implies that the renal impairment may be transitory in some patients.